Economic evaluation of supplementation with Canavalia brasiliensis CIAT 17009 in a Colombian dual-purpose cattle system - Junca-Paredes, John Jairo; Mojica Rodríguez, José Edwin; Sotelo-Cabrera, Mauricio Efren; Castro Rincón, Edwin; Burkart, Stefan (Frontiers Media, 2025)
Introduction In the dual-purpose cattle systems of the Colombian Caribbean region, the grass Bothriochloa pertusa (Colosuana) is predominant. Despite its overall good performance, its productivity and quality significantly decline during dry seasons, leading to feed shortages and production slumps. Supplementation with legumes and improvement of pasture conditions are effective measures to address these challenges, but their adoption remains low in the region, which, among others, is related to limited availability to information on both legume cultivation and conservation, seed scarcity, and financial constraints. Methods Against this background and with the purpose of contributing to closing the information gap, this study provides an economic assessment to determine the feasibility of adopting pasture improvement measures and legume hay supplementation. Based on information from agronomic evaluations conducted by AGROSAVIA, the economic analysis compares a traditional dual-purpose grazing system ( Bothriochloa pertusa monoculture) with 3 improved systems that contemplate both pasture improvement of Bothriochloa pertusa and supplementation with hay of the legume Canavalia brasiliensis at 3 different inclusion levels (0.5, 1.0, 1.5% dry matter of animal liveweight). Results and discussion The results show that pasture improvement and supplementation significantly improve the productivity of the production system and thus its economic performance, as documented by improved financial indicators, such as the Net Present Value, Internal Rate of Return, or Benefit–Cost Ratio.